High flux strontium atom source - Feng, C. H. (2024)
We present a novel cold strontium atom source designed for quantum sensors. We optimized the deceleration process to capture a large velocity class of atoms emitted from an oven and achieved a compact and low-power setup capable of generating a high atomic flux. Our approach involves velocity-dependent transverse capture of atoms using a two-dimensional magneto-optical trap. To enhance the atomic flux, we employ tailored magnetic fields that minimize radial beam expansion and incorporate a cascaded Zeeman-slowing configuration utilizing two optical frequencies. The performance is comparable to that of conventional Zeeman slower sources, and the scheme is applicable to other atomic species. Our results represent a significant advancement towards the deployment of portable and, possibly, space-based cold atom sensors.